(untitled) (Salud, Arte y Cuidado, 2017)
Bartholinitis is the inflammation of the Bartholin´s glands, located on both sides of the vagina, between the labia majora and the wall of the vagina, and whose function is vaginal lubrication. When Bartholin´s gland is blocked, the liquid which it naturally produces is accumulated and a round lump begins to form at the edge of the vagina. When there is infection, the lump is filled with a purulent liquid of very unpleasant odor. The present investigation aims to identify domains and affected classes to a patient who suffers from Bartolinitis and Myiasis. Materials and Methods: A case study of a 24-year-old female patient who was diagnosed with Bartolinitis and Myiasis, an invasive treatment was applied at a public health institution in the city of Barquisimeto, State Lara, Venezuela. The nursing process was applied, nursing assessment was performed with the Nursing Diagnostics Taxonomy II, the domains and affected classes were described, and the nursing care plan was implemented with the diagnostic interrelationships, interventions and results. Results: The patient progressed favorably, she was discharged ten days after the nursing intervention was applied. training was provided for her care at home. Conclusions: At the end of the investigation of the case, it was observed the importance of carrying out the nursing care plan with the respective interrelationships to provide quality care.